Kajian Perkembangan Teknologi Jaringan 5G dan Tantangan Implementasinya di Kota Padang - Rio Agus Saputra; Yulindon Yulindon (Kampus Akademik Publiser, 2026)
The fifth-generation (5G) mobile communication network represents a significant advancement in telecommunications by providing higher data transmission speeds, lower latency, greater network capacity, and support for massive Internet of Things (IoT) connectivity. These capabilities are expected to accelerate digital transformation across various sectors, including education, healthcare, transportation, manufacturing, and public services. Nevertheless, the implementation of 5G technology in Indonesia remains uneven, particularly outside major metropolitan areas.This study aims to examine the development of 5G technology and identify the challenges associated with its implementation in Padang City. The research employs a qualitative descriptive approach through a literature review by analyzing scientific articles, government reports, publications from telecommunication operators, and international standards related to 5G technology. The findings indicate that although Padang possesses considerable potential for 5G deployment due to increasing internet demand and ongoing digital transformation initiatives, several challenges persist. These include limited infrastructure readiness, high investment costs, spectrum allocation issues, regulatory constraints, and disparities in digital infrastructure.The study concludes that collaboration among government institutions, telecommunication operators, academia, and industry is essential to accelerate 5G deployment in Padang. Strategic infrastructure planning, investment incentives, spectrum optimization, and human resource development are recommended to maximize the benefits of 5G technology. Keywords: 5G Network, Telecommunications, Digital Transformation, Padang City, Implementation Challenges